2019
DOI: 10.1111/ggi.13839
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia and pneumonia in older people

Abstract: Pneumonia is a major cause of death in older people, and the number of such deaths is increasing. Present guidelines for pneumonia management are based on a pathogen‐oriented strategy that relies on the optimal application of antibiotics. Older pneumonia inpatients show the high incidence of aspiration pneumonia. The main cause of aspiration pneumonia is an impairment in the swallowing and cough reflexes. These facts suggest a limitation of present management strategies and a requirement for new strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 88 publications
1
110
2
Order By: Relevance
“…undernutrition [4][5][6]. In the complex geriatric context, Okazaki and colleagues (2019) recently presented the concept of "vicious circle of aspiration pneumonia" where sarcopenia, undernutrition, and inflammation are at the core of recurrent aspiration pneumonia [7]. Sarcopenia is recognized as a syndrome characterized by a progressive and generalized loss of skeletal muscle mass and strength, with a risk of adverse outcomes, such as physical disability, poor quality of life and death [8].…”
Section: Introductionmentioning
confidence: 99%
“…undernutrition [4][5][6]. In the complex geriatric context, Okazaki and colleagues (2019) recently presented the concept of "vicious circle of aspiration pneumonia" where sarcopenia, undernutrition, and inflammation are at the core of recurrent aspiration pneumonia [7]. Sarcopenia is recognized as a syndrome characterized by a progressive and generalized loss of skeletal muscle mass and strength, with a risk of adverse outcomes, such as physical disability, poor quality of life and death [8].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction C ommunity and hospital acquired pneumonia is still one of the major lethal causes in Japan, especially in aged generations, (1)(2)(3)(4)(5)(6)(7) whereas several preventive medical practices including vaccination for pneumonia have been performed. (8)(9)(10) In aged populations, majority of community acquired pneumonia might be caused by aspiration and/or dysphagia, which might lead to a high recurrence rate and poor prognosis of the disease.…”
mentioning
confidence: 99%
“…Studies have shown that skeletal muscle mass is a predictor of mortality in ICU patients and patients with aspiration pneumonia [18]. A decrease in muscle mass and strength especially in swallowing related muscles may affect the prognosis of pneumonia in older patients [19]. The majority of infections in our study were pneumonia and the most deaths were due to infections.…”
Section: Discussionmentioning
confidence: 56%